2022
DOI: 10.3390/life12030334
|View full text |Cite
|
Sign up to set email alerts
|

A Fast-Growing Oleaginous Strain of Coelastrella Capable of Astaxanthin and Canthaxanthin Accumulation in Phototrophy and Heterotrophy

Abstract: Considering the importance of microalgae as a promising feedstock for the production of both low- and high-value products, such as lipids and pigments, it is desirable to isolate strains which simultaneously accumulate these two types of products and grow in various conditions in order to widen their biotechnological applicability. A novel freshwater strain from the genus Coelastrella was isolated in Belgium. Compared to other Coelastrella species, the isolate presented rapid growth in phototrophy, dividing 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…The surface topology of the cells was visible in SEM images, the cells exhibiting meridional ribs that run from one pole to the other ( Figure 1 d). These features have been described for other Coelastrella species and are evidently typical of the genus [ 18 , 20 , 21 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The surface topology of the cells was visible in SEM images, the cells exhibiting meridional ribs that run from one pole to the other ( Figure 1 d). These features have been described for other Coelastrella species and are evidently typical of the genus [ 18 , 20 , 21 , 23 , 24 ].…”
Section: Resultsmentioning
confidence: 61%
“…KGU-H001 [ 16 ], Coelastrella terrestris [ 17 ], Coelastrella astaxanthina sp. nov. [ 18 ], as well as several other Coelastrella isolates [ 19 , 20 , 21 ]. Indeed, it has been suggested that Coelastrella could be a viable candidate for commercial production of carotenoids.…”
Section: Introductionmentioning
confidence: 99%
“…In the conditions tested, D14 displayed a doubling time of 2.6 days (Table S1). A novel freshwater Coelastrella strain isolated in Belgium, presented a rapid growth in phototrophy, with a doubling-time of 6.8 ± 0.30 h hours at a light intensity of 400 µmol·m −2 ·s −1 and 5% CO 2 (Corato et al, 2022). The specific growth rate seems to depend on dosing times of the carbonic solution added to the culture unless indoor.…”
Section: Discussionmentioning
confidence: 99%
“…Glass beads were added to the sample and cells were disrupted through horizontal agitation in a TissueLyser II (Qiagen, Hilden, Germany) for 2 × 5 min at 30 Hz. Fatty Acid Methyl Esters (FAMEs) were generated from the microalgal biomass as described in Corato et al (2022) . FAMEs quantification was performed using gas chromatography (GC, Shimadzu, Tokyo, Japan) and a flame ionization detector (FID, Shimadzu) as mentioned in Gérin et al (2020) .…”
Section: Methodsmentioning
confidence: 99%